Microbial and chemical stability of Acheta domesticus powder during one year storage period at room temperature - Marzoli, Filippo; Tata, Alessandra; Zacometti, Carmela; Malabusini, Serena; Jucker, Costanza; Piro, Roberto; Ricci, Antonia; Belluco, Simone (Frontiers in Sustainable Food Systems, 2023)
The sustainability of food systems is of growing concern worldwide, so insects are a growing source of animal proteins for food and feed. Among insect species, the house cricket, Acheta domesticus, is a promising option from a sustainability point of view. This study aimed at evaluating both microbiological and chemical stability of A. domesticus powders during one year of storage at room temperature. Our study was conducted on cricket powders obtained by three different processes: drying at 80°C (P80), drying at 120°C (P120), and lyophilization (PL). Regarding microbiological profile, the pathogens Listeria monocytogenes and Salmonella were not detected, while total viable count and lactic acid bacteria tended to decrease during the storage period. Bacillus cereus was detected at low counts during the entire storage period, but only one replicate of P80 exceeded the limit set for A. domesticus by the European Commission Implementing Regulation 2017/2470. The measured protein contents of the cricket powders immediately after production ranged between 60.6 and 64.3%. The peroxide values were far higher than the limit established by the EU Regulation in all samples. Higher amounts of hexanal and pentanal were detected in P80 and P120 than in PL, indicating that oven drying could enhance lipid oxidation. In conclusion, a one year shelf-life can suitably be ascribed to the analyzed cricket powders from a microbiological point of view, but lacked chemical stability and had a clear early tendency toward rancidity. The samples dried at 120°C and lyophilized never exceeded the limit set by European Commission for B. cereus count in A. domesticus powder. In addition, lyophilized samples showed the lowest values of hexanal and pentanal, the aldehydes that are primarily responsible for the rancid smell. The oxidative status of the final products could be strongly influenced by the powder processing, so for this reason, edible insect species-specific post-rearing protocols should be implemented. These results open an interesting scenario for a long period of storage of insect powder in the absence of a cold chain, making the insect market an increasingly sustainable sector.